(untitled) (Scientific journal of the Fergana State University, 2023)
The article analyzes Remarque’s war-related works, in particular, the novels “All Quiet on the Western Front” “Three Comrades” and “The Night of Lisbon”. The author’s skills in using typical images and creating character’s art are studied.